(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Shade matching is a significant process in fixed dental prosthesis where the selection needs special attention and systemic approach in covering all aspects. It is a fact that this approach is mainly used for achieving the goals related to the morphological and optical acceptance within the community settings. A total of 960 patients were taken and analysed for shade matching in fixed partial denture. The data collection is done from the dental archives of the patient management software system. The study is done under university setting. The results were analysed using SPSS software version 20 by IBM.T he result observed is that there is a highly achieved shade match with positive correlation and significant values (p<0.05) in the fixed partial denture patients. From the overall study it was found that quality of shade match in fixed partial dentures is clinically good. Special attention and effort to be performed during shade selection to get accurate shade match in fixed dental prosthesis.